Research on the Teacher Appointment System of Colleges and Universities - Zhang, Jing; Li, Jingfu; Li, Furong; Wang, Baoyu; Qiu, Dong (Journal of Educational Research and Policies, 2025)
The appointment system of teachers in higher education institutions is a new employment system that has the advantages of maintaining the vitality of the teaching staff and promoting the optimization and renewal of the teaching staff. However, there are still some problems that need to be further improved. This paper analyzes the problems existing in the current appointment system of teachers in higher education institutions. Furthermore, corresponding reform measures are proposed for different problems, and relevant measures are explained with examples. It is hoped that the suggestions put forward can further improve and promote the healthy development of the appointment system of teachers in higher education institutions.